The Use of Artificial Intelligence Techniques in Smart Classrooms is in Its Infancy - Elena Figueroa; Edgar Batista; Ramon Palau; Oihane Unciti; Maria Ferre; Antoni Martinez-Balleste (IEEE Access, 2024)
Smart classrooms are physical learning spaces that, using data from the environment, students and teachers, are able to provide timely and valuable information to improve teaching and learning processes and foster decision-making. In this article, we provide an overview of how artificial intelligence techniques are being used to gain insights into the teaching and learning processes by analyzing data not only from the classroom context, but also from students and teachers. We identify the latest literature addressing the use of artificial intelligence techniques with data obtained from the smart classroom, present a taxonomy for the areas of application, review the state of deployment in schools, and discuss the current limitations. From the results, we conclude that the use of artificial intelligence techniques to analyze classroom data in real settings (i.e., primary and secondary schools) is still far from common. Most proposals are in the lower range of technological readiness levels and do not consider issues such as information security and privacy. Furthermore, most proposals focus on the development of technological products and do not address their impact on learning. Our paper concludes with an outlook on future work in this area with the aim of making the smart classroom a cornerstone for the future of education.